D. Carlos de Bragança, a pioneer of experimental marine oceanography: filling the gap between formal and informal science education - Faria, Cláudia (2011)
The activities presented in this paper are part of a wider project that investigates the effects of infusing the history of science in science teaching, toward students’ learning and attitude. Focused on the work of D. Carlos de Braganc¸a, King of Portugal from 1889 to 1908, and a pioneer oceanographer, the activities are addressed at the secondary Biology curriculum (grade 10, ages 15, 16). The proposed activities include a previsit orientation task, two workshops performed in a science museum and a follow-up learning task. In class, students have to analyse original historical excerpts of the king’s work, in order to discuss and reflect about the nature of science. In the museum, students actively participate in two workshops: biological classification and specimen drawing. All students considered the project relevant for science learning, stating that it was important not only for knowledge acquisition but also for the understanding of the nature of science. As a final remark we stress the importance of creating activities informed by the history of science as a foundation for improving motivation, sustaining effective science teaching and meaningful science learning, and as a vehicle to promote a closer partnership between schools and science museums.